2012
DOI: 10.1128/jcm.05400-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Hybrid Capture 2 and cobas 4800 Tests for Detection of High-Risk Human Papillomavirus in Specimens Collected in PreservCyt Medium

Abstract: Clinical cervical cytology specimens (n ‫؍‬ 466) collected in PreservCyt (Hologic Inc.) were used to evaluate the agreement between Hybrid Capture 2 (hc2; Qiagen) and cobas 4800 (c4800; Roche Molecular Diagnostics) for the detection of high-risk human papillomavirus (HR HPV) genotype infections. The agreement between the two assays was 93.8% (kappa ‫؍‬ 0.87; 95% confidence interval, 0.828 to 0.918), with 186 and 251 concordant positive and negative results, respectively. All 186 concordant positives were confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
5
28
1
3
Order By: Relevance
“…Since HC2 is the most commonly used HPV test and recommended as a standard, we included this test at baseline with cobas 4800 HPV testing simply to obtain comparative data. The agreement of 85.1% that we observed, although at a lower range of reported agreements, was still consistent with the overall published data (11)(12)(13)(14)(15)(16). However, as the study utilized pooled samples, no cytology or histology results could be obtained to correlate with the above-described HPV testing results.…”
Section: Stability Of Cervical Specimenssupporting
confidence: 80%
“…Since HC2 is the most commonly used HPV test and recommended as a standard, we included this test at baseline with cobas 4800 HPV testing simply to obtain comparative data. The agreement of 85.1% that we observed, although at a lower range of reported agreements, was still consistent with the overall published data (11)(12)(13)(14)(15)(16). However, as the study utilized pooled samples, no cytology or histology results could be obtained to correlate with the above-described HPV testing results.…”
Section: Stability Of Cervical Specimenssupporting
confidence: 80%
“…In addition, the Cobas HPV test demonstrated a sensitivity (91.7%) and specificity (97.0%) between those of the other two assays. In recently published studies, Cobas HPV also showed comparable performances to HC2, with kappa coefficients from 0.69 to 0.87, but there also were discrepant results between HC2 and Cobas HPV in approximately 6% to 15% of the samples (10,20,34). In another recent study, Cobas HPV showed a clinical sensitivity of 89.7% and a specificity of 66.7% for detecting cases with CIN2 or worse-grade CINs, whereas HC2 demonstrated a better clinical sensitivity of 93.1% and a specificity of 72.2% (18).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the Abbott RealTime HR HPV assay was introduced to clinical laboratories, demonstrating performances comparable with those of HC2 (4,16,24,33). In April 2011, the Roche Cobas HPV assay, which also utilizes the real-time PCR principle, was approved by the U.S. FDA for detecting HR HPVs, and a few studies compared the results obtained by Cobas HPV with those of HC2 (10,20,34). However, there are currently no published studies in the literature which concurrently evaluated HC2, RealTime HR, and Cobas HPV assays.…”
mentioning
confidence: 99%
“…However, the cobas® Test also detects genotype 66 and indicates specifically whether the specimen is positive or negative for HPV-16 or HPV-18. 55 The strong association of cervical cancer with these two genotypes is the basis for a primary HPV screening strategy in which women who test positive for HPV-16/HPV-18+ genotypes are triaged directly for colposcopy. In ATHENA, genotyping for HPV-16/HPV-18 improved the sensitivity for CIN3+ and required far fewer cytology tests with only a marginal increase in colposcopies over co-testing.…”
Section: Discussionmentioning
confidence: 99%